The Effect of Work Placement on Increasing Employee Productivity at Sharia Multi Finance Cibarusah - Ermi Herawati; Supriatal; Ali Mutaufiq (International Journal of Sharia Business Management, 2022)
This study aims to determine the effect of work placement on increasing work productivity of sharia multi-finance employees Cibarusah. This research is quantitative research, using the associative method. The sample used was 38 people. The technique used by the author is saturated sampling where the entire population is sampled. Data collection techniques in this study were interviews, observation, questionnaires, and literature study. Testing the instrument using validity and reliability tests, and for data analysis methods using frequency distribution analysis, simple linear regression, correlation coefficient, coefficient of determination, and t test. data calculation is done by using statistical software. The results showed that the job placement in the frequency distribution analysis was perceived as quite good at 3.65 with a class interval table (3.53-3.72). The increase in productivity in the analysis of the frequency distribution is perceived as good at 3.68 with the class interval table (3.56-3.77). The results of the simple linear regression analysis obtained in this study are Y = 29.978 + 0.631X. It can be interpreted that if there is no effect of work placement (X = 0), the Productivity Increase is worth 29.978 units. However, if there is an increase of 1 unit/unit of the Work Placement variable (X=1), it will affect the increase in Productivity (Y) of 0.631 units. The correlation coefficient is perceived as strong as 0.629, while the coefficient of determination of 39.6% and 60.4% is influenced by several factors not included in this study. While the results of the analysis of the hypothesis test (t test) with the result that is 4.857 > t table value of 2.028 so that Ho is rejected and Ha is accepted. This means that there is a significant effect between work placement and the increase in the work of sharia multi finance employees Cibarusah.